Synthesis and Thermal Degradation Behaviours of Novel Phosphorus-Containing Polyurethane Elastomers - Xu, Wenzong; Yin, Jianguo; Hu, Yuan; Lu, Bo; Hung, Wei (Asian Journal of Chemistry, 2012)
Phenyl diaminophosphate was synthesized based on phenyl dichlorophosphate and characterized by Fourier transform infrared spectroscopy and nuclear magnetic resonance. Phenyl diaminophosphate was used as chain extender to prepare a series of phosphorus containing polyurethane elastomers (PPUEs) with different phosphorus contents by changing the soft segments. The thermogravimetric analyses result reveal that the char yield of PPUEs is much higher: the char yield of PPUE1 reaches 35 % whose phosphorus content is just 1.5 %, indicating that the phosphorus contributes to the improved char-forming ability. The microscale combustion colorimeter (MCC) result shows that the PPUEs show better flame retardancy and the flame retardant of the polyurethane elastomer increases with the phosphorus content increasing. The degradation kinetics studies show that the degradation of polyurethane elastomers is divided into two stages, where the activation energy of PPUEs in their first stage is lower than that of corresponding polyurethane elastomers based on 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), but the activation energy in the second stage is higher.